Decreased expression of nemo-like kinase in melanoma is correlated with increased vascularity and metastasis. Issue 4 (August 2019) - Yang, Yvying; Zhe, Hong; Massoumi, Ramin; Ke, Hengning
Abstract : Melanoma is a highly metastatic cancer, and its incidence has increased over the past several decades. Angiogenesis is associated with melanoma metastasis and a poor prognosis. Many genetic and epigenetic factors affecting tumour vascularization and metastasis have been investigated, despite the heterogeneity of cancer cells and the complicated mechanisms involved in melanoma. Nemo-like kinase (NLK) is a serine/threonine kinase regulating the transcription factor by negatively regulating Wnt and downstream vascular endothelial growth factor receptor 2 (VEGFR2) signalling. This study aimed to investigate whether NLK expression in melanoma correlates with VEGFR2-related angiogenesis and melanoma metastasis. Immunohistochemistry analysis using 175 biopsied tissues of melanoma patients showed that NLK is expressed in 73.7% of melanoma tissues, whereas 26.3% of the samples showed absent expression of NLK. In metastatic melanoma, the expression of NLK was significantly lower than that in primary melanoma ( P = 0.002). Furthermore, tissues with a lower expression of NLK showed a higher microvessel density as detected by VEGFR2 expression compared with tissues showing higher NLK expression. These data suggest that reduced expression of NLK in melanoma correlates with VEGFR2-related microvessel formation and melanoma metastasis. This study showed that NLK may serve as a novel prognosis marker and revealed new mechanisms in melanoma metastasis.